2023
DOI: 10.7759/cureus.46486
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Heart Failure Management: A Comprehensive Narrative Review of Emerging Therapies

FNU Sapna,
FNU Raveena,
Maria Chandio
et al.

Abstract: Heart failure is a substantial and escalating global health challenge, affecting millions worldwide. This complex syndrome arises from diverse etiologies, encompassing ischemic heart disease, hypertension, valvular abnormalities, and cardiomyopathies. Heart failure is characterized by the heart's inability to pump blood efficiently to meet the body's metabolic demands, leading to debilitating symptoms, frequent hospitalizations, and high mortality rates. Traditionally, the management of Heart failure has focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…They are crucial in identifying problems such as anastomotic leakage, gastrointestinal bleeding, or airway anomalies. These imaging techniques provide a thorough diagnostic approach, allowing healthcare professionals to visualize and define postoperative problems correctly [31].…”
Section: Imaging and Diagnostic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are crucial in identifying problems such as anastomotic leakage, gastrointestinal bleeding, or airway anomalies. These imaging techniques provide a thorough diagnostic approach, allowing healthcare professionals to visualize and define postoperative problems correctly [31].…”
Section: Imaging and Diagnostic Toolsmentioning
confidence: 99%
“…Delays in recognizing complications are caused by insufficient monitoring, inconsistencies in healthcare professional alertness, and communication obstacles specific to the patient. The lack of protocols for postoperative care impedes uniformity in clinical practice [31]. Differences in care methods among healthcare practitioners and institutions can result in discrepancies in preventing and managing complications.…”
Section: Challenges In Managing Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, using mesh in hernia repair procedures brought about a fundamental change, resulting in a notable decrease in hernia recurrence. In the first stages, the mesh was utilized using synthetic substances, specifically polypropylene, to reinforce the debilitated abdominal wall further [31]. Although there were initial achievements, worries about consequences such as infection and adhesion development led to the continuous improvement of mesh materials.…”
Section: Evolution Of Contemporary Approachesmentioning
confidence: 99%
“…Studies have shown that the Extended Totally Extraperitoneal (eTEP) method has recurrence rates ranging from 1% to 3%, indicating its efficiency in repairing long-lasting hernias [39]. The eTEP technique is generally linked with a low incidence of complications, with reported rates of infection, seroma development, and chronic discomfort ranging from 1% to 3% [31]. These percentages emphasize the significance of precise surgical technique and careful patient selection to maximize results.…”
Section: Complications and Challengesmentioning
confidence: 99%